Developing Microsoft Sway-Based Interactive Media in Pigmented Facial Care to Increase Motivation and Outcomes - Poernamasari, Diyah Ayu Catur; Purwanto, Eko; Sugiyo Pranoto, Yuli Kurniawati (Innovative Journal of Curriculum and Educational Technology, 2022)
The suboptimal use of learning media and students’ difficulty in understanding the material are the reasons why Microsoft sway-based interactive media is developed. This research aims to increase motivation and learning outcomes through interactive multimedia using Microsoft sway. The research applied the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) because it is structured, rational, and complete steps for developing learning media. The result showed that 1) the step of developing interactive multimedia using Microsoft Sway was according to the students' and teachers' need analysis which required audio-visual media. The interactive multimedia design using Microsoft sway was systematically depicted in the flowchart and the development was illustrated in detailed capture. The evaluation from material and media experts said that this interactive multimedia was feasible. 2) The implementation of Microsoft Sway-based interactive media was according to the schedule, 3) The students’ learning outcomes taught with Microsoft sway-based interactive multimedia were better than taught with conventional media, 4) Microsoft sway-based interactive multimedia improved student motivation. The result of this study described that this developing interactive media was effective to improve learning outcomes and it can be beneficial for teachers as the alternative media in beauty class.